Low-dose Computed Tomography Screening in Japan. Issue 2 (March 2015) - Nawa, Takeshi; Nakagawa, Tohru; Mizoue, Tetsuya; Endo, Katsuyuki
Abstract : Lung cancer is a leading cause of cancer death in both male and female individuals in Japan. The effect of screening using chest radiography is assumed to be limited. In Japan, screening using low-dose computed tomography (CT) was initiated in 1993, and its dissemination has progressed with studies evaluating its efficacy, although it is not officially recommended. In addition to the academic activities of the Japanese Society of CT Screening, certification of physicians and radiologic technologists by the Japan Accreditation Council for CT Screening has been progressing. Currently, several hundred thousand low-dose CT screenings are performed annually in Japan. In Hitachi City, Ibaraki Prefecture, low-dose CT screening among employees and in communities started in 2001, and it was estimated that 40% of 50- to 69-year-old citizens had undergone screening at least once by March 2009. The lung cancer mortality rate in citizens in this age group decreased by 24% in 2005 to 2009 compared with the national statistics. Low-dose CT screening targeting the general population may be effective, but it is necessary to consider the target and interval of screening separately from those for the high-risk group. Observational study may play a role in evaluating the efficacy of screening in Japan.